Numerical Modelling and Damage Assessment Criteria for FRP-Retrofitted RC Columns - Inês Sousa; Rita Peres; Rita Couto; Rita Bento; José Miguel Castro (Buildings)
The numerical modelling procedures and damage criteria of both existing and retrofitted reinforced concrete (RC) elements are crucial for reliable seismic assessment and the retrofitting of existing RC buildings. A widely used retrofitting technique involves the application of fiber-reinforced polymers (FRPs) to vulnerable RC elements, enhancing their flexural and shear capacities. However, the current version of EC8-3 does not explicitly provide guidelines for numerical modelling, nor does it offer specific information on the assessment of retrofitting elements. This study focuses on developing a concentrated plasticity modelling approach and defining the damage state criteria for retrofitted RC columns with FRPs, based on experimental data from the literature. A database comprising 99 FRP-retrofitted RC columns was compiled, and regression analysis procedures were used to calibrate the peak load rotation, ultimate rotation, and post-capping rotation capacities. The modelling approach was validated through comparison with existing formulations using OpenSees, and the results indicate its adequacy for the seismic assessment of retrofitted buildings. This research advances the seismic assessment of FRP-retrofitted RC elements by introducing a novel trilinear moment–rotation model and refined damage criteria, which provide higher predictive accuracy in comparison to existing proposals. It also addresses critical gaps in seismic assessment practices by proposing the peak load rotation as a more reliable SD limit state threshold for retrofitted columns.